MUTU DODOL PISANG BERDASARKAN SUBTITUSI BERBAGAI JENIS PISANG (Musa paradisiaca) - Elvis Eriyana; Husain Syam; Jamaluddin P Jamaluddin P (Universitas Negeri Makassar, 2017)
This study aims to determine the effect of substitution of various types of bananas on the quality of bananas dodol and also to determine the organoleptic quality bananas and also to determine the organoleptic quality dodol bananas. This study uses five types of bananas including ambon bananas, barangan of bananas, raja of bananas, tanduk of bananas and kepok of bananas. This study uses a completely randomized design CRD) and the data were analyzed using microsoft excel and SPSS version 22. The parameters observed in this study is the water content, reducing sugar and hedonic sensory organoleptic quality. The results showed that the banana dodol made from ambon of bananas is the best of the quality and organoleptic test results